Analysis of Waste Management Integration within the GPBLHS Framework in Grade XI Chemistry Curriculum - Indri Gus Permata Sari; Nurhasan Syah; Aulia Azhar; Ratna Wilis (Postgraduate, University of Mataram, 2026)
Environmental Education (EE) is interdisciplinary and contextual because it connects natural sciences, social sciences, and humanities to build a holistic understanding of environmental issues. This approach enables students to connect academic concepts with real-world phenomena in the school and community, making learning more meaningful and applicable. This study aims to analyze the integration of waste management within the School Environmental Care and Culture Movement (GPBLHS) into Chemistry learning for Grade 11 students at SMA Pembangunan Laboratorium UNP, in terms of the implementation process, challenges, support from the school's physical condition, and its impact on students' environmental awareness and behavior. The study uses a multidisciplinary mixed-methods approach. The study uses quantitative data as the primary approach, supported by qualitative data. Data were collected through Likert-scale questionnaires, observations, interviews, and document analysis, then analyzed using descriptive statistics, linear regression, and thematic analysis. The results showed that waste management integration has been implemented through contextual learning but has not been systematically integrated into the curriculum. Key challenges include limited teacher understanding, minimal training, and suboptimal utilization of infrastructure. This integration has had a positive impact on increasing students' awareness and tendency to care for the environment.